Multicomponent, high-intensity, and patient-centered care intervention for complex patients in transitional care: SPICA program - García-Hernández, Miguel; González de León, Beatriz; Barreto-Cruz, Silvia; Vázquez-Díaz, José Ramón (Frontiers in Medicine, 2022)
Multimorbidity is increasingly present in our environment. Besides, this is accompanied by a deterioration of social and environmental conditions and affects the self-care ability and access to health resources, worsening health outcomes and determining a greater complexity of care. Different multidisciplinary and multicomponent programs have been proposed for the care of complex patients around hospital discharge, and patient-centered coordination models may lead to better results than the traditional ones for this type of patient. However, programs with these characteristics have not been systematically implemented in our country, despite the positive results obtained. Hospital Universitario de Canarias cares for patients from the northern area of Tenerife and La Palma, Spain. In this hospital, a multicomponent and high-intensity care program is carried out by a multidisciplinary team (made up of family doctors and nurses together with social workers) with complex patients in the transition of care (SPICA program). The aim of this program is to guarantee social and family reintegration and improve the continuity of primary healthcare for discharged patients, following the patient-centered clinical method. Implementing multidisciplinary and high-intensity programs would improve clinical outcomes and would be cost-effective. This kind of program is directly related to the current clinical governance directions. In addition, as the SPICA program is integrated into a Family and Community Care Teaching Unit for the training of both specialist doctors and specialist nurses, it becomes a place where the specific methodology of those specialties can be carried out in transitional care. During these 22 years of implementation, its continuous quality management system has allowed it to generate an important learning curve and incorporate constant improvements in its work processes and procedures. Currently, research projects are planned to reevaluate the effectiveness of individualized care plans and the cost-effectiveness of the program.